Post total thyroidectomy, isolated right side chylothorax with high output fistula managed with lymphangiography - Dhruva Sharma; Deven Juneja; Omender Singh; Amit Goel; Prashant Singh; Varun Arora (Indian Journal of Respiratory Care, 2021)
Chylothorax is a rare complication after total thyroidectomy with radical neck dissection, and isolated right side chylothorax is even rarer. Treatment may be conservative or surgical. Besides being helpful in making a diagnosis, thoracic duct lymphangiography (TDL) may be therapeutic in some cases. However, its application in high output chylous leak is not fully explored. Here, we present a rare case of right-sided high output chylothorax, secondary to total thyroidectomy, successfully treated with TDL.